Novel, cold-adapted D-laminaribiose- and D-glucose-releasing GH16 endo-β-1,3-glucanase from Hymenobacter siberiensis PAMC 29290, a psychrotolerant bacterium from Arctic marine sediment - Kim, Do Young; Lee, Yung Mi; Lee, Jong Suk; Chung, Chung-Wook; Son, Kwang-Hee (Frontiers in Microbiology, 2024)
Endo-β-1,3-glucanase is a glycoside hydrolase (GH) that plays an essential role in the mineralization of β-glucan polysaccharides. In this study, the novel gene encoding an extracellular, non-modular GH16 endo-β-1,3-glucanase (GluH) from Hymenobacter siberiensis PAMC 29290 isolated from Arctic marine sediment was discovered through an in silico analysis of its whole genome sequence and subsequently overexpressed in Escherichia coli BL21. The 870-bp GluH gene encoded a protein featuring a single catalytic GH16 domain that shared over 61% sequence identity with uncharacterized endo-β-1,3-glucanases from diverse Hymenobacter species, as recorded in the National Center for Biotechnology Information database. The purified recombinant endo-β-1,3-glucanase (rGluH: 31.0 kDa) demonstrated peak activity on laminarin at pH 5.5 and 40 o C, maintaining over 40% of its maximum endo-β-1,3-glucanase activity even at 25 o C. rGluH preferentially hydrolyzed Dlaminarioligosaccharides and β-1,3-linked polysaccharides, but did not degrade D-laminaribiose or structurally unrelated substrates, confirming its specificity as a true endo-β-1,3-glucanase without ancillary GH activities. The biodegradability of various substrate polymers by the enzyme was evaluated in the following sequence: laminarin > barley β-glucan > carboxymethyl-curdlan > curdlan > pachyman. Notably, the specific activity (253.1 U mg -1 ) and catalytic efficiency (kcat/Km: 105.72 mg - 1 s -1 mL) of rGluH for laminarin closely matched its specific activity (250.2 U mg -1 ) and kcat/Km value (104.88 mg -1 s -1 mL) toward barley β-glucan. However, the kcat/Km value (9.86 mg -1 s -1 mL) of rGluH for insoluble curdlan was only about 9.3% of the value for laminarin, which correlates well with the observation that rGluH displayed weak binding affinity (<40%) to the insoluble polymer. The biocatalytic hydrolysis of D-laminarioligosaccharides with a degree of polymerization between 3 and 6 and laminarin generally resulted in the formation of D-laminaribiose as the predominant product and D-glucose as the secondary product, with a ratio of approximately 4:1. These findings suggest that highly active rGluH is an acidic, cold-adapted D-laminaribiose-and D-glucose-releasing GH16 endoβ-1,3-glucanase, which can be exploited as a valuable biocatalyst for facilitating low temperature preservation of foods.